Alginate / Polyvinyl Alcohol / Bentonite Hydrogel Beads for Cu (II) Adsorption - Miftakhul Ulumiah; Mochammad Amin Alamsjah; Patmawati (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research Hydrogel bead based on alginate, PVA and bentonite were prepared by ionic gelation. Hydrogel bead were tested on Cu standard solution and waste water from paper industry. Adding bentonite on hydrogel bead plays a key role for Cu removal. Hydrogel bead show selective removal on waste water containing Cu, Pb and Cr. Abstract Heavy metal pollution is a major problem for most water areas. One way to remove heavy metal ions is through the adsorption process by using combination of alginate / polyvinyl alcohol hydrogel. Adding bentonite can make good adsorption and effective. The purpose of this study was to analyze the effect of hydrogels for adsorption of heavy metals Cu (II) in liquid waste from paper industrial. This study used a Completely Randomized Design (CRD) experimental method with 5 treatments and 3 replications. Types of treatments include control treatments and the addition of bentonite with a ratio of 0.5 - 1.25%. The best treatment will be applied to liquid waste. The results showed that hydrogel beads from alginate / polyvinyl alcohol / bentonite have significant differences between treatments on the adsorption of heavy metal Cu (II). The best treatment was the addition of 1% bentonite (P4) with an adsorption capacity of 74.43%. The results of the application on liquid waste showed the following adsorption capacity: Cr (65.13%) > Cu (60.84%) > Pb (44.47%). Suggestions that can be given for further research are the application of hydrogel beads to other heavy metals that have the potential to increase adsorption capacity, such as Cr.